Debt management in India - Singh, Charan (Economist) (Cambridge : Cambridge University Press, 2018)
This book is a comprehensive analysis of the implications of rising public debt in India. It specifically investigates the implications of domestic debt on consumption, the effect of monetised debt on prices, the long-term relationship between domestic debt and growth, and the separation of debt and monetary management. It studies data on debt in India from 1951 to 2017, and covers a wide canvas of issues related to debt management and important developments in the government securities market. It discusses trends in domestic debt, and provides a descriptive review of the major components of public debt. The book presents a close theoretical discussion on the Ricardian equivalence hypothesis, an important concept both historically and in contemporary literature on public debt. The implications of domestic debt delineated in the objectives are empirically analysed.
Title from publisher's bibliographic system (viewed on 16 Nov 2018).
Keywords: Ricardo, David, -- 1772-1823.; Debts, Public -- India; Economic development -- India; Rational expectations (Economic theory)